Immersive virtual reality for unintentional injury prevention training with children: A systematic review - Allana Santiago; Bernadette Matthews; Won Sun Chen; Therese Keane; Jordy Kaufman (Computers & Education: X Reality)
Researchers and educators continue to explore the potential of Immersive Virtual Reality (IVR) technology for safety training in children, as unintentional injuries persist as the leading cause of global mortality among this cohort. In order to implement IVR as a safety training tool, it is important to understand its effectiveness compared to other methods. However, few studies have systematically summarised the use of IVR for unintentional injury prevention training with children. To address this gap, a systematic review was conducted using five databases, following the PRISMA guidelines. Sixteen studies published until March 2024 were identified that evaluated the effectiveness of IVR technology for unintentional injury prevention training with children aged 1–14 years. We evaluated: i) the types of unintentional injury skills taught, ii) research designs, data collection methods and measures used, iii) IVR interface and equipment utilised, and iv) the effectiveness of IVR technologies in comparison to conventional methods of training. The majority of the identified studies focused on road safety, with three on fire safety, and one on water safety. Varied instruments were used to measure outcomes including knowledge, behaviour, immersion, interest, enjoyment, and usability. IVR interventions employed head-mounted displays (N = 13) and Cave Automatic Virtual Environments (N = 3), with either interactive or passive experiences. Overall, the studies suggest a positive role for IVR in unintentional injury prevention training with children. However, only two studies made direct comparisons with other methods, underscoring the need for a cautious interpretation of the findings. Future studies should prioritise evaluating the transfer of learnings from the virtual environment to real-world settings, direct comparisons between IVR and conventional training methods, the relationship between different IVR learning approaches and cognitive and motor skill acquisition, and the correlation between immersion and learning outcomes.